Diseminasi Disinfektan Covid-19 Pembangkit Listrik Tenaga Surya Pada Masjid Baitul Muttaqiin Pucu’An - Jamaaluddin Jamaaluddin; Izza Anshory; Shazana Dhiya Ayuni (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
In this kind of COVID-19 pandemic, prevention is very necessary. The forms of the prevention process from the dangers of COVID-19 are spraying disinfectants regularly and continuously. Spraying of disinfectants is carried out in many public places / public facilities such as worship facilities, tourist attractions, offices and others. In this community service, the prevention efforts will be applied to the Baitul Muttaqiin mosque in Pucu'an village. Baitul Muttaqiin Pucukan Mosque is a mosque located at the eastern end of Sidoarjo Regency. This mosque needs attention because it is located at the end of Sidoarjo and difficult to transport. The location can only be reached by motorbike or boat. By using energy sources from Solar Power Plants.  This Solar Power Plant is managed by a Solar Charge Controller and a water pump, so spraying this disinfectant can be done without incurring electricity costs. Photovoltaic systems with a power of 50 Wattpeak as many as 3 units are regulated by the Solar Charge Controller utilizing batteries as solar energy storage will be able to operate the system properly. Disinfectant ingredients and how to operate the system are taught to residents around the mosque. This system turned out to be very effective to be used as an effort to prevent the development of COVID-19 in general areas of worship in particular and to hamlet residents in general.